Transcriptional factor EB regulates macrophage polarization in the tumor microenvironment. (4th May 2017) - Fang, Liang; Hodge, Johnie; Saaoud, Fatma; Wang, Junfeng; Iwanowycz, Stephen; Wang, Yuzhen; Hui, Yvonne; Evans, Trent D.; Razani, Babak; Fan, Daping
ABSTRACT: Tumor microenvironment (TME) contains a variety of infiltrating immune cells. Among them, tumor-associated macrophages (TAMs) and their alternative activation contribute greatly to the progression of tumors. The mechanisms governing macrophage polarization in the TME are unclear. Here, we show that in TAMs or macrophages under tumor-conditioned medium treatment, the expression of transcription factor EB (TFEB) is reduced and more of the TFEB protein is in an inactive cytosolic form. Transforming growth factor (TGF)-β is identified as a main driving force for the reduced TFEB expression and activity in TAMs via activating ERK signaling. TFEB interference in macrophages significantly enhanced their alternative activation, with reduced expression of MHC-II and co-stimulatory molecule CD80, decreased ability to activate T cells, and increased ability to attract tumor cells. When co-inoculated with tumor cells, macrophages with TFEB knockdown significantly enhanced tumor growth with increased infiltration of M2-like macrophages, reduced infiltration of CD8 + T cells, and enhanced angiogenesis in the tumors. Mechanistic studies revealed that TFEB downregulation resulted in macrophage M2 polarization through reducing SOCS3 production and enhancing STAT3 activation. We further demonstrate that the activation of TFEB by hydroxypropyl-β-cyclodextrin in macrophages suppressed their M2 polarization and tumor-promoting capacity, and that macrophage-specific TFEB overexpression inhibited breast tumor growth in mice. Therefore, our data suggest that TFEB plays critical roles in macrophage polarization, and the downregulation of TFEB expression and activation is an integral part of tumor-induced immune editing in the TME. This study provides a rationale for a new cancer treatment strategy by modulating macrophage polarization through activating TFEB.